Modelling of Noise Influence on the Characteristics of Multiphase Signals on the Example of the Signal Based on the Generalized Frank Code - Yankevych, Roman (Видавництво Львівської політехніки, 2012)
This paper is devoted to the problem of noises influence on the complex multiphase signals that could be used as probing signals in the radar systems.
Keywords: Complex multiphase signals; optimal processing; generalized Frank code; signal-to-noise ratio